2021
DOI: 10.1007/s11270-021-05282-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Biogas Residue Acidification and Nitrification Inhibitors in Mitigating CO2 and N2O Emissions from Biogas Residue-Amended Soils

Abstract: Owing to their high carbon and nitrogen contents, biogas residues may lead to higher carbon dioxide (CO2) and nitrous oxide (N2O) emissions from soils. Acidification of biogas slurry and application of nitrification inhibitors (NIs) could mitigate the emission of these gases. An incubation experiment was therefore carried out to investigate the effect of NIs, DMPP (3, 4-dimethylpyrazole phosphate), and PIADIN (active ingredients: 3.00–3.25% 1,2,4-triazole and 1.50–1.65% 3-methylpyrazole), on CO2 and N2O emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Differences between sampling systems may be inherent to the sampling methodology, chamber design (probably a minor factor in our study because the chamber dimensions were relatively similar for both systems), length of deployment (Kandel et al, 2017) and the number of data points (Hüppi et al, 2018; Parkin et al, 2012). Both older and more recent studies of N 2 O emissions from soil have used linear regression as the only way to calculate N 2 O fluxes (Christensen et al, 2021; Guo et al, 2021; Pugesgaard et al, 2017; Smith & Dobbie, 2001). The large differences that can be introduced by using different methodologies for flux estimation (Levy et al, 2011) have the potential to invalidate attempts at integrating results from different experiments, for example for the purpose of modelling, or for comparisons of the N 2 O mitigation potential of different agricultural practices in meta analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between sampling systems may be inherent to the sampling methodology, chamber design (probably a minor factor in our study because the chamber dimensions were relatively similar for both systems), length of deployment (Kandel et al, 2017) and the number of data points (Hüppi et al, 2018; Parkin et al, 2012). Both older and more recent studies of N 2 O emissions from soil have used linear regression as the only way to calculate N 2 O fluxes (Christensen et al, 2021; Guo et al, 2021; Pugesgaard et al, 2017; Smith & Dobbie, 2001). The large differences that can be introduced by using different methodologies for flux estimation (Levy et al, 2011) have the potential to invalidate attempts at integrating results from different experiments, for example for the purpose of modelling, or for comparisons of the N 2 O mitigation potential of different agricultural practices in meta analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The CO 2 -C, N 2 O-N, and CH 4 -C samples were collected once a day during the first week, once per two days during the second week, and once per three days during the last two weeks (Guo et al, 2021a). The pots were first closed by adding lids, gases were mixed by collecting and injecting the gas in and out of the pots a few times with a syringe, and then samples were collected from the headspace at 0, 30, and 60 min after lid closure (Guo et al, 2021b). A 20-ml syringe and hypodermic needle was used to collect the gas samples and inject them into pre-evacuated 12-ml glass headspace exetainer vials fitted with a chloro-butyl rubber septum (Guo et al, 2022a).…”
Section: Collection and Measurement Of Ghgsmentioning
confidence: 99%
“…These residues are derived from anaerobically digested organic wastes and contain a range of macro and micronutrients in readily available forms for plants. They have been found to improve soil quality, plant productivity, and resilience to biotic and abiotic stress agents (Guo et al, 2021;Mdlambuzi et al, 2021). However, studies have also shown that due to their high carbon (C) and ammonium (NH 4 + ) content, BR can lead to even higher CO 2 and N 2 O emissions as well as nitrate (NO 3 − ) leaching from the soils compared to mineral fertilisers (Senbayram et al, 2009;Eickenscheidt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%